Mapping progress and challenges for women’s empowerment in the Global South - Lelea, ﻿Margareta Amy (Faculty of Social Sciences and Humanities, UKM,Bangi, 2012)
﻿This mapping of patterns and trends in the Global South reveals that some progress has been made in terms of declining maternal mortality rates, increasing educational access and literacy for women, and increasing participation in the labour force by women. However, there are also immense challenges to be faced such as HIV/AIDS, human trafficking, and the feminisation of poverty that are affecting more women. Additionally, the regionalised spatial variations that can be observed when mapping and reviewing gender-differentiated quality of life indicators show that the reality faced by women in the Global South is uneven with respect to sex ratio, life expectancy at birth, international migration, fertility rate, infant mortality , literacy, labour force participation, HIV/ AIDS infection, parliamentary presence, and the Global Gender Gap. The overriding implication is that for there to be progress towards women’s empowerment in the Global South recognition of the possibility, continuing demanding and pressing for change, and working towards it, are critical to the whole process.